Tear identitário:a prática docente em arte como conhecimento compartilhado - Coelho, Pollyanna Jerico Pinto (2010)
This investigative tissue is about the formation of identification processes of teachers and pedagogical practice of Art, in Teresina city. This search comprised the sum of the needs presented, agreed upon with the teachers engaged in the process, it was developed through the establishment of interactive environment Loom Team where collaboration and critical reflection were steering actions to promote the understanding of existing connections or relations within the processes of identifications and the pedagogical practice of Art. The tissue is formed by the polyphonic plot of the critical reflection of nine teachers of Art who engaged voluntarily and this investigation of formative nature and a production of knowledge. All these teachers have degree and the course of artistic education and especial qualification in Fine Arts and/or Drawing. The texture, which we denominated Identification Loom: The pedagogical practice of Art as share knowledge is (de) (re) construction of knowledge resulting from the critical reflection, in an environment of collaboration, which may have implications and ethical political attitudes in the pedagogical practice of the group. Within this context, we pose the following question: - How does the pedagogical practice in Art influence and/or be influenced by the identification processes of the teachers, and how do they interfere with the search and manifestation of the knowledge involved and the investment in professionalization? In view of this query, we make use of the cooperative investigation, having social history as theoretical reference and as analytic perspective of interactive and dialogical-reflexive processes. Thus, social historic theory, cooperative approach and pedagogical practice were the major components of the plot. The methodological texture counted on the threads of dialogical reflexion, of mediation and of collaboration. The conceptual formulation, the recording in videos of classes and the narratives of formations were the main threads of the analytic substrate of the investigation. With this articulation, theses threads appear as developers of processes leading to a major approximation of the thought on the identity/alterity dialectical pair of the participants involved. The language within this plot had a decisive importance in all the moments of the search of signification, embracing and connecting the identification/alterative processes, the pedagogical practice of Art and the knowledge shared. In such processes involving (de) (re) construction, one can notice a close correlation of the triad social identity, pedagogical practice and knowledge shared. For this reason, the vigotskian, guetmanovian and kopnian theoretizations were the major framework for the analysis of conceptual formulations; and, as for discourse analysis, Baktin and Orlandi were our masters. For these teachers, the experience shared throughout the process of this typology of tri-axial investigation focused the experience of many theoretical and practical assumptions. Such an experience enabled them to state that this, with collaboration, can make reflection on the practice a starting and promoting element, within the individual level of self-management, in addition to being a space of (de)(re)construction of meanings, of knowledge and of reinvention per se